Psychological and Academic Predictors of Employability Skills: The Mediating Role of Career Planning in Indonesian Engineering Students - Muhammad Haristo Rahman; Nahridzah Mahjubuh Shiber; Aminuddin (Academic Bright Collaboration, 2026)
Purpose – This study examines the psychological and academic antecedents of employability skills among engineering students by investigating the roles of self-efficacy and academic commitment, with career planning as a mediating variable.Methods – A quantitative cross-sectional survey was conducted with 323 undergraduate engineering students from a public university in Indonesia. Validated instruments were used to measure self-efficacy, academic commitment (level of commitment, investment, and meaningfulness), career planning, and employability skills (analytical skills, general management, and leadership). Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Findings – The findings showed that self-efficacy and academic investment were the most consistent predictors of career planning. In turn, career planning was positively associated with all dimensions of employability skills, indicating its central role as a mediating mechanism between psychological and academic factors and employability outcomes. By contrast, level of commitment and meaningfulness showed weaker and less consistent relationships with employability dimensions.Research implications – The findings highlight the importance of strengthening self-efficacy, promoting active academic investment, and integrating structured career planning into higher education to support students’ employability development. Originality – This study extends prior employability research by testing a mediated model of self-efficacy, academic commitment, and career planning in an Indonesian engineering student context. However, the findings should be interpreted cautiously due to the cross-sectional design and single-university sample.